Effect of raspberry extract on wound healing. (23rd June 2021) - Lu, Wenjing; Xu, Meng; Yuan, Youwei; Zhang, Xuemei; Tan, Jianxin; He, Junping; Tian, Yiling
Abstract: The main purpose of this study was to investigate the effect of raspberry extract on wound healing and compare it with that of ellagic acid. The elimination of excess free radicals was the key to preventing wound inflammation; cellular antioxidation activity was evaluated using an oxidative stress damage cell model. Cell proliferation ability was measured using the WST-1 assay, and the migration capacity was determined using the wound scratch assay. A mouse wound model was used to verify the effect of raspberry extract on wound healing. The cellular antioxidant activity of the extract ((50.31±3.17) μg/mL) was slightly lower than that of ellagic acid ((44.59±2.38) μg/mL). The results of a cell proliferation assay showed that both raspberry extract and ellagic acid at 5 μg/mL could significantly ( P <0.01) promote the proliferation of HaCaT cells. After culturing for 24 h and 48 h, the cell healing rates of the extract were (41.11±0.38) per cent and (68.88±2.51) per cent, respectively, whereas the corresponding rates of ellagic acid were (39.01±2.40) per cent and (70.33±0.89) per cent; hence, there were no significant differences between them ( P >0.05). The wound areas of mice fed low, medium, and high doses of raspberry extract for 14 days were 1.66, 1.41, and 1.24 mm 2, respectively, which were significantly lower than that of the blank control group, 2.18 mm 2 ( P <0.05). These findings indicate that raspberry extract and ellagic acid exhibit similar antioxidant capacities and equivalent cell proliferation-promoting capabilities. In the mouse test, raspberry extract effectively promoted a reduction in wound area. This work demonstrates the potential of raspberry extract in wound healing, suggesting a promising application of raspberry resources in the fields of functional foods, cosmetics, and medicine.